Robust composite nonlinear feedback for nonlinear Steer-by-Wire vehicle’s Yaw control - Sarah 'Atifah Saruchi; Mohd Hatta Mohammed Ariff; Hairi Zamzuri; Noraishikin Zulkarnain; Mohd Hanif Che Hasan; Sheikh Muhammad Hafiz Fahami (Institute of Advanced Engineering and Science, 2019)
Yaw control is a part of an Active Front Steering (AFS) system, which is used to improve vehicle manoeuvrability. Previously, it has been reported that the yaw rate tracking performance of a linear Steer-by-Wire (SBW) vehicle equipped with a Composite Nonlinear Feedback (CNF) controller and a Disturbance Observer (DOB) is robust with respect to side wind disturbance effects. This paper presents further investigation regarding the robustness of the combination between a CNF and a DOB in a nonlinear environment through a developed 7-DOF nonlinear SBW vehicle. Moreover, in contrast to previous studies, this paper also contributes in presenting the validation works of the proposed control system in a real-time situation using a Hardware-in-Loop (HIL) platform. Simulation and validation results show that the CNF and DOB managed to reduce the influence of the side wind disturbance in nonlinearities.